2006
DOI: 10.1128/aem.72.2.1218-1225.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the tre Locus and Analysis of Trehalose Cryoprotection in Lactobacillus acidophilus NCFM

Abstract: Freezing and lyophilization are common methods used for preservation and storage of microorganisms during the production of concentrated starter cultures destined for industrial fermentations or product formulations. The compatible solute trehalose has been widely reported to protect bacterial, yeast and animal cells against a variety of environmental stresses, particularly freezing and dehydration. Analysis of the Lactobacillus acidophilus NCFM genome revealed a putative trehalose utilization locus consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 42 publications
(42 reference statements)
6
51
1
1
Order By: Relevance
“…In contrast, FOS and raffinose are transported by ABC transporters of the MsmEFGK family, La502-La505 and La1437-La1442, respectively. In the case of trehalose and FOS, microarray results correlate well with functional studies in which knock out of transporters and hydrolases modified the saccharolytic potential of L. acidophilus (9,21). Differential expression of the EIIABC Tre is consistent with recent work in L. acidophilus, indicating that La1012 is involved in trehalose uptake, because knock out of the trehalose PTS transporter resulted in a loss of the ability to grow on trehalose (21).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, FOS and raffinose are transported by ABC transporters of the MsmEFGK family, La502-La505 and La1437-La1442, respectively. In the case of trehalose and FOS, microarray results correlate well with functional studies in which knock out of transporters and hydrolases modified the saccharolytic potential of L. acidophilus (9,21). Differential expression of the EIIABC Tre is consistent with recent work in L. acidophilus, indicating that La1012 is involved in trehalose uptake, because knock out of the trehalose PTS transporter resulted in a loss of the ability to grow on trehalose (21).…”
Section: Discussionsupporting
confidence: 84%
“…In the case of trehalose and FOS, microarray results correlate well with functional studies in which knock out of transporters and hydrolases modified the saccharolytic potential of L. acidophilus (9,21). Differential expression of the EIIABC Tre is consistent with recent work in L. acidophilus, indicating that La1012 is involved in trehalose uptake, because knock out of the trehalose PTS transporter resulted in a loss of the ability to grow on trehalose (21). Similarly, differential expression of the fos operon is consistent with previous work in L. acidophilus indicating that those genes are involved in uptake and catabolism of FOS, induced in the presence of FOS, and repressed in the presence of glucose (9).…”
Section: Discussionsupporting
confidence: 69%
“…Analysis of the L. acidophilus NCFM genome revealed that a putative trehalose utilization locus consisting of a transcriptional regulator (treR), a trehalose phosphoenolpyruvate transferase system transporter (tre-B) and a trehalose-6-phosphate hydrolase (treC). It was demonstrated that disruption of both the hydrolase genes and trehalose transporter abolished the ability of L. acidophilus NCFM to grow on trehalose and reduced the survival of this microorganism when subjected to repeated cycles of freezing and thawing in the presence of trehalose, demonstrating that not only is the internalization of trehalose important, but also its subsequent hydrolysis is an important contributing factor (Duong et al, 2006). It has been demonstrated that different bacterial species vary with respect to spray-drying tolerance, indicating the importance of strain selection.…”
Section: Important Parameters Affecting Microencapsulationmentioning
confidence: 99%
“…The L. acidophilus NCFM genome was recently sequenced to reveal that the molecular machinery responsible for carbohydrate uptake and catabolism in NCFM accounts for 17% of the genes present in the genome (23). Broad carbohydrate utilization of L. acidophilus NCFM was demonstrated and included transporters for trehalose (24), fructooligosaccharides (25), and several other mono-, di-, and trisaccharides (26).…”
mentioning
confidence: 99%